Development of a Web-Based Canteen Delivery Application Using QR-Code and SAW Method at Untag Surabaya: Pembuatan Aplikasi Pesan Antar dengan Penerapan QR-Code di Kantin Untag Surabaya Berbasis Web Menggunakan Metode Simple Additive Weighting - Reza Galang Kurniawan; Roenadi Koesdijarto (JOINCS (Journal of Informatics, Network, and Computer Science), 2025)
The system developed is a web-based delivery application that uses QR-Codes to indicate the order location containing a link to the ordering website and the order's pickup point. This research aims to develop the application for the cafeteria at Universitas 17 Agustus 1945 Surabaya, recommending popular foods that are often bought utilizing the Simple Additive Weighting (SAW) approach based on parameters like price, taste, service, and portion size. The results show that the application functions according to specifications, with all features operating correctly and being responsive to user input. Testing with 30 respondents using the UMUX Lite method resulted in an average score of 80.497, indicating that the application falls within the acceptable category. This application is expected to be well-implemented in the Untag Surabaya cafeteria, providing convenience and efficiency in ordering and transactions, and contributing to the development of web and mobile-based information systems using the SAW method and QR-Code technology.